On not writing back: Cosmopolitan paradoxes in new diasporic Malaysian writing today. Issue 5 (3rd September 2021) - Lee, Jason Eng Hun; Iyer, Sreedhevi
ABSTRACT: In this article, two contemporary writers, Jason Eng Hun Lee and Sreedhevi Iyer, combine to reflect on emerging issues in their writing practice as deterritorialized writers with connections to Malaysia. Unlike earlier generations of post-independence writers, neither Lee nor Iyer "writes back" to the former colonial centre nor, despite their designation as "Malaysian writers" by commercial publishers, do they "write back" to their condition as sectional writers in the Malaysian literary canon. Instead, taking on a confessional mode, the two writers examine the paradox of their cosmopolitan sensibilities in an age of deterritorialized national literatures. Iyer reflects on her story collection Jungle Without Water, and her use of vernacular Malaysian English to transcend cultural explication, while Lee draws on his poetry collection Beds in the East to suggest how a double perspective that pivots between Malaysia and the UK can strategically mediate the colonial/postcolonial gaze.